2014
DOI: 10.1186/preaccept-5559348291243054
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in newborn care and newborn resuscitation following a quality improvement program at scale: results from a before and after study in Tanzania

Abstract: BackgroundEvery year, more than a million of the world’s newborns die on their first day of life; as many as two-thirds of these deaths could be saved with essential care at birth and the early newborn period. Simple interventions to improve the quality of essential newborn care in health facilities – for example, improving steps to help newborns breathe at birth – have demonstrated up to 47% reduction in newborn mortality in health facilities in Tanzania. We conducted an evaluation of the effects of a large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…[33][34][35] In our study, the difference between the higher prevalence of provision of signal functions and higher quality of services in EmOC compared with EmNC was due to the lack of two signal functions: KMC and provision of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] In our study, the difference between the higher prevalence of provision of signal functions and higher quality of services in EmOC compared with EmNC was due to the lack of two signal functions: KMC and provision of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…18,36,39,48,59,62 All but 1 of these studies showed that significantly increased BMV use (83.3%) persisted after training compared with before training; however, application of this life-saving maneuver was far from universal, and the technique was often incorrect. In a study from Tanzania's HBB program, only 21.5% of trained participants correctly demonstrated all 3 maneuvers to improve BMV 6 weeks after training.…”
Section: Retention Of Bmv Skillsmentioning
confidence: 99%
“…36,37,43,44,59 Of these, 4 studies (80.0%) found that high or low test scores accurately predicted clinical behavior, 37,43,44,59 and only 1 study (20.0%) reported improved test scores but reduced use of stimulation and longer time to BMV initiation in the delivery room at 7 months after training. 36 Nine studies (20%) attempted to correlate performance on either standardized tests or actual behavior in the delivery room with changes in neonatal mortality statistics, and the results were mixed.…”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a pre-post study in Tanzania found significant improvements in health worker knowledge of neonatal resuscitation yet skills did not improve. 33 This suggests that improved knowledge alone is insufficient to ensure the adoption of guidelines.…”
Section: Discussionmentioning
confidence: 99%